2009
DOI: 10.3200/htps.87.1.3-9
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives From Nurse Leaders and Chief Information Officers on Health Information Technology Implementation

Abstract: To enhance the limited empirical evidence in the literature, the authors developed new knowledge and information on the basis of implementation experiences (e.g., strategic planning, goals, outcomes, barriers, mistakes) of hospital executives with actual health information technology (HIT). The authors asked why hospital leaders implement HIT and how they do so, and then applied the answers to the theoretical framework of change management and leadership. The authors accomplished this through a qualitative res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 2 publications
0
27
0
Order By: Relevance
“…The importance of leaders' support was also detected by Hsia et al [50], who found that top management beliefs support HIT usage in the organisation. Not only is top management support important, but clinical leaders and middle managers also act as supporters [33,35,39,47]. Abbott [6] recognised the role of leaders as champions, and in this role they had the knowledge, skills and understanding of the complexities of HIT, and they were passionate about implementation and better health outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of leaders' support was also detected by Hsia et al [50], who found that top management beliefs support HIT usage in the organisation. Not only is top management support important, but clinical leaders and middle managers also act as supporters [33,35,39,47]. Abbott [6] recognised the role of leaders as champions, and in this role they had the knowledge, skills and understanding of the complexities of HIT, and they were passionate about implementation and better health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…According to the included studies, the most common role for healthcare leaders in HIT implementation was that of supporter [33][34][35][38][39][40][41][42]47,48]. Leaders at all levels were responsible for supporting HIT implementation [33,35,39,47]. When leaders did not support implementation, it struggled to succeed [41].…”
Section: Role Of Supportermentioning
confidence: 99%
See 1 more Smart Citation
“…Information system (IS) applications have enabled many organisations to become more productive and competitive in the 21st century (Ashrafi and Mueller, 2015;Johnson and Lederer, 2013;Li et al, 2013b;Luftman, 2003;Szydlowski and Smith, 2009;Yeh and Teng, 2012), through IS resources and IS capabilities (Ashrafi and Mueller, 2015). However, while there are many IS success stories, many failures have also been reported (Akgün et al, 2014;Barker and Frolick, 2003;Dawson and Owens, 2008;Lech, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The lack of information technology staff with EHR knowledge and training is a large barrier to EHR use. 6,7 Low patient volume with high overhead cost and trends to increased outpatient services that provide lower reimbursement than inpatient services generate an RH environment of limited finances and resources. 8 Using Structured Query Language (SQL), a data manipulation language developed by the International Standards Organization and the International Electrotechnical Commission (both Geneva, Switzerland), provides a mechanism whereby complex but specific data can be retrieved from the EHR, which are not available otherwise and are not supplied by the EHR's vendor.…”
mentioning
confidence: 99%